Analisis Rekrutmen dan Pengembangan Kualitas Guru Pendidikan Khusus di Sekolah Inklusif di Kota Banjarmasin - Yanti, Yuli; Ahsan Romadlon Junaidi; Ediyanto (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the recruitment system, selection mechanisms, and professional development for special education teachers in Banjarmasin City using an explanatory sequential research design. In the first stage of the research, quantitative data was collected through questionnaires distributed to special education teachers. The sampling technique used in this study was probability sampling with simple random sampling. The sample size was determined based on the Slovin formula with an error margin of 5%, which was 60 special education teachers. Next, qualitative data was collected through interviews, observations, and documentation with relevant stakeholders. The data analysis techniques used in the qualitative research stage were (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusion drawing. The quantitative research results revealed that most of the respondents were women aged 25–34 years, had a bachelor's degree in special education, and had more than five years of teaching experience in positions of honor. Correlation analysis showed a moderate positive relationship (r = 0.502) between the recruitment system and teacher professional development, which contributed 25.2% (R² = 0.252). These findings confirm that a good recruitment system can improve teacher professionalism, which ultimately supports the success of inclusive education. Meanwhile, qualitative results show that the recruitment of special education teachers in Banjarmasin follows regional regulations by involving the education office and inclusive schools. Although a bachelor's degree in special education is preferred, the limited number of graduates requires flexibility in the recruitment process. The main challenges include budget constraints and the lack of qualified teachers, thus requiring supportive policies, increased funding, and collaboration with universities to improve the quantity and quality of teachers. Professional development is carried out through various training programs, but still faces obstacles in the form of budget constraints and the lack of a continuous evaluation system.